The Influence of a Self-Compassion Training Program on Romantic Relationship Conflict: An Exploratory Multiple-Case Study - Budzan, Brittany N.; Van Vliet, K. Jessica (Canadian Journal of Counselling and Psychotherapy, 2021)
Separation and divorce are common occurrences in the Western world. Given that a transition out of a marriage can increase psychological distress in the members of the couple as well as in their children, preventive interventions are crucial for avoiding serious ruptures and for increasing relationship strength and resilience. A potential option for clinicians is to use interventions designed to increase self-compassion. This multiple-case study explored the influence of a self-compassion intervention on conflict within romantic relationships. Three women completed a self-compassion training CD, six sets of online questions, and two semi-structured interviews. Thematic analysis was used to construct detailed accounts of each participant’s experience. Participants perceived that self-compassion helped them to de-escalate conflict, increase self-awareness and self-acceptance, and facilitate perspective taking. This study may help inform future relationship interventions.